Transforming Healthcare Delivery: AI-Powered Clinical Decision Support Systems - Atul Ramesh Bharmal (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Integrating Artificial Intelligence in Clinical Decision Support Systems (CDSS) has fundamentally transformed healthcare delivery by enhancing diagnostic accuracy, improving treatment outcomes, and streamlining clinical workflows. This comprehensive article explores the key features, benefits, implementation challenges, and future innovations in AI-powered CDSS. Through examination of real-world implementations across multiple healthcare institutions, this article demonstrates how advanced algorithms, multimodal data integration, and automated analysis capabilities are revolutionizing clinical decision-making. The article highlights significant improvements in diagnostic accuracy, reduced medical errors, and enhanced patient outcomes while addressing critical challenges in data quality, workflow integration, regulatory compliance, and clinician acceptance. Furthermore, the article explores emerging technologies, including federated learning, ambient clinical intelligence, and extended reality integration, providing insights into the future evolution of healthcare decision support systems.